Uncommon Histopathological Variants of Malignant Melanoma: Part 1. (April 2019) - Cota, Carlo; Saggini, Andrea; Lora, Viviana; Kutzner, Heinz; Rütten, Arno; Sangüeza, Omar; Requena, Luis; Cerroni, Lorenzo
Abstract : Abstract: Despite new horizons opened by recent advances in molecular pathology, histological evaluation still remains the diagnostic gold standard regarding cutaneous melanocytic neoplasms. Several histological variants of melanoma have been described, and their knowledge is crucial for accurate diagnosis and classification of cases with unusual clinicopathological features. Uncommon histological variants of melanoma have been described based on a broad constellation of features, including architectural pattern, stromal alterations, cytological attributes, and other morphological properties. This review is aimed at providing an extensive discussion of unusual but distinctive histopathological variants of melanoma.